2022
DOI: 10.5194/isprs-annals-x-4-w3-2022-57-2022
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection and Dimensional Measurement of Minor Concrete Cracks With Convolutional Neural Network

Abstract: Abstract. The increasing number of aging infrastructures has drawn attention among the industry as the results caused by critical infrastructure failure could be destructive. It is essential to monitor the infrastructure assets and provide timely maintenance. However, one of the crucial problems is that the budget allocated to the maintenance stage is much less than that for the designing and construction stages. The cost of labor, equipment, and vehicles are significant. Therefore, it is impossible to perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…After testing, it was found that adding Batch Norm between Convolution and ReLU could improve performance. The proposed convolutional neural network model is adjusted for concrete cracks [54].…”
Section: Pixel Level Semantic Segmentation For Defectmentioning
confidence: 99%
“…After testing, it was found that adding Batch Norm between Convolution and ReLU could improve performance. The proposed convolutional neural network model is adjusted for concrete cracks [54].…”
Section: Pixel Level Semantic Segmentation For Defectmentioning
confidence: 99%